التركيبة الطائفية والاجتماعية في لبنان قبل عام 1922م. - الفجر، فهد إمسلم زغير (الجامعة المستنصرية - كلية الآداب, 2021)
لقد حاولنا في بحثنا الموسوم (التركيبة الطائفية والاجتماعية في لبنان قبل عام 1922) تتبع الجذور التأريخية العميقة للطائفة في لبنان وولادة أول كيان سياسي طائفي في المشرق العربي، فقد عد لبنان من أكثر الأقطار العربية تعقيداً وتنوعاً من حيث واقعة الأثني، إن ما يهمنا في هذا البحث هو الحقبة التي تبلورت فيها الطائفية مؤثراً على جوانبها الاجتماعية والسياسية والاقتصادية، وبدأت تصبح جزءاً لا يتجزأ من مكونات المجتمع اللبناني، أن مشكلة لبنان الحالية ليست طائفية بقدر ما هي مشكلة التدخلات الأجنبية، والطائفية في أكثر الاحتمالات هي الشعور الخفي أو المعلن الذي يدفع إحدى الطوائف لاعتبار مصلحتها تفوق أو تتقدم على مصالح الطوائف أو الفئات الأخرى.
We tried in our entitled research (the racist and social composition in Lebanon before the year 1922) follows the deep racist roots through the history. And the birth of the first political and racist party or direction in the Arabic orient, as a result to that Lebanon can be considered as one of the most complicated and varying according the ethnic fact. But, we're interested too much in the period which had developed the racist at the expense of the social, politic and economical facts in this country, to be as a part and parcel from the Lebanese society composition. The current Lebanese problem cannot be considered as a racist as much as the problem of the international interventions which can be racist In the most of the whole cases as a probability which came by the hidden or the declared feeling which made one of the various denomination in this country his own purposes on the account on the other denominations' goods and purposes.
Keywords: التركيبة الاجتماعية -- الطوائف الأثنية -- التدخلات الأجنبية -- المجتمع اللبناني